Fulfillment Of Restitution Rights In The Level Of Investigation In The Semarang Big City Resort Police In Beating Criminal Case - Aris Sophian; Umar Ma'ruf; Aryani Witasari (Jurnal Daulat Hukum, 2020)
The purpose of this study was to determine and analyze the granting of restitution rights in the handling of beatings, the implementation of restitution rights in the handling of beatings in the Semarang Big City Resort Police Department, as well as the obstacles faced and solutions in granting restitution rights in the handling of beatings in the Semarang Big City Resort Police.This study uses empirical juridical research methods, with descriptive analytical research specifications, the data used in this study are secondary data, obtained through literature studies and primary data obtained through field research which are then analyzed qualitatively using the theory of legal certainty, theory of law enforcement .The results of this study are: (1). The implementation of restitution rights at the level of investigation in the handling of beatings in the Semarang Big City Resort Police Department. Efforts to grant restitution rights at the investigation level should investigators choose and sort out which cases can be given restitution rights at the investigation level so that victims of criminal offenses receive compensation accordingly with what has been suffered by the victims of the crime and the case can be completed in the level of investigation with peace between the victim and the suspect. (2). Obstacles and solutions in granting restitution rights in the handling of beatings at the level of investigation in the Semarang Big City Resort Police Department,Keywords: Restitution Rights; Beating Crime; Semarang Big City Resort Police.